Pelecehan Seksual sebagai Alasan Perceraian: Studi Kasus di Desa Katibung Kecamatan Sidomulyo Kabupaten Lampung Selatan - Adila Maria Ulfa; Abdul Qodir Zaelani; Kartika S (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Sexual harassment within the family occurs as a social reality in Katibung Village, Sidomulyo District, South Lampung Regency. The case involves a wife pregnant with her first child who experienced sexual harassment from her stepfather-in-law. The husband failed to defend his wife, causing her to return to her parents' home and refuse to go back due to trauma. This prolonged separation eventually led to talak and official divorce at the Religious Court. This study examines: (1) forms of sexual harassment as grounds for divorce including chronology and impact, and (2) the legal position of sexual harassment as groundsfor divorce in Islamic family law. This research employs a qualitativenorm tive-empirical field research approach with in-depth interviews of four informants selected by purposive sampling. Results show that sexual harassment during pregnancy caused dharar threatening the victim's life, intellect, and honor. In Islamic family law, this contradicts Maqāṣid asy-Syarī‘ah, making the talak and divorce legally valid.